Characteristics of carcinoembryonic antigen-producing colorectal cancers: A population based study - Groover, Sarah; Kaul, Rashmi; Johnston, Sarah E; Zhao, Yan D; Karippot, Asha; Thirunavukarasu, Pragatheeshwar (Archive of Oncology, 2019)
Objectives: Serum carcinoembryonic antigen is a tumor marker often found to be elevated in colorectal cancer patients. Elevated carcinoembryonic antigen has been strongly associated with poor prognosis. However, little is known about the patient and tumor characteristics between carcinoembryonic antigen -secreting and non- -secreting tumors. Methods: We performed a retrospective analysis of all patients (N=164,187) in the Surveillance, Epidemiology and End Results database diagnosed with colorectal adenocarcinoma from 2010 to 2014. All patients were designated as having either positive/elevated (C1) or negative/normal (C0) pretreatment serum carcinoembryonic antigen level. Results: Of the 164,187 patients, 68,833 (57.0%) had available carcinoembryonic antigen information, and 33,412 (48.5%) had positive/elevated (C1) antigen levels. Median age was 65 years, and 36,464 (53.0%) were male. Patients with C1 cancers were more likely to be female (Odds ratio 1.06), black (Odds ratio 1.62), separated or never married (Odds ratios 1.50 and 1.49, respectively), higher grade (Odds ratios 1.35, 1.64, and 1.72 of moderately, poorly, and undifferentiated cancers, respectively), and of signet ring cell histology (Odds ratio 1.47) compared to males, whites, married participants, well differentiated grade, and adenocarcinoma histology respectively (P<0.001). Multivariate analysis showed that non-Caucasian race, female gender, unmarried status, distal to sigmoid colon location, increasing tumor invasion beyond muscular layer, increasing nodal involvement, and presence of metastases were independent factors associated with the C1 diagnosis. Conclusions: About half of all colorectal adenocarcinomas are associated with elevated pre-treatment serum carcinoembryonic antigen levels. Our study is the first nationwide population-based study quantifying the prevalence of serum carcinoembryonic antigen elevation in the colorectal cancer population, and identifying patient and tumor characteristics associated with elevated carcinoembryonic antigen.